2016 ACC/AHA Clinical Performance and Quality Measures for Adults With Atrial Fibrillation or Atrial Flutter: A Report of the American College of Cardiology/American Heart Association Task Force on Performance Measures. (July 2016) - Heidenreich, Paul A.; Solis, Penelope; Mark Estes, N. A.; Fonarow, Gregg C.; Jurgens, Corrine Y.; Marine, Joseph E.; McManus, David D.; McNamara, Robert L.
Abstract : Supplemental Digital Content is available in the text.